Infectious spleen and kidney necrosis virus induces the reactive oxidative species/Nrf2-mediated oxidative stress response for the regulation of mitochondrion-mediated Bax/Bak cell death signals in GF-1 cells - Chen, Pin-Han; Hsueh, Tsai-Ching; Hong, Jiann-Ruey (Frontiers in Microbiology, 2022)
IInfectious spleen and kidney necrosis virus (ISKNV) infections can trigger host cell death and are correlated with viral replication; however, they have rarely been considered in terms of the host organelle involvement. In the present study, we demonstrated that ISKNV triggered an oxidative stress signal in the Nrf2-mediated oxidative stress response and induced stress signals for Bax/Bak-mediated host cell death in fish GF-1 cells. The results showed that after ISKNV infection, the levels of reactive oxidative species (ROS) increased by 60-80% from day 3 to day 5, as assessed by an H2DCFDA assay for tracing hydrogen peroxide (H2O2), which was correlated with up to a one-fold change in the fish GF-1 cells. Furthermore, we found that ISKNV infection induced Nrf2-mediated ROS stress signals from D1 to D5, which were correlated with the upregulation of antioxidant enzymes, such as catalase, SOD1, and SOD2; these effects were blocked by the antioxidants GSH and NAC. By analyzing Nrf2-mediated ROS stress signals for cell death regulation via an apoptotic assay, we found that treatment with antioxidants reduced annexin-V-positive signals by 10% (GSH) to 15% (NAC); moreover, necrotic-positive signals were reduced by 6% (GSH) and 32% (NAC) at day 5 (D5) in GF-1 cells, as indicated by PI staining. Furthermore, we found that Nrf2-mediated ROS stress regulated mitochondrion-mediated Bax/Bak death signals at D3 and D5; this was effectively blocked by antioxidant treatment in the GF-1 cells, as demonstrated by a JC1 assay (ΔΨm) and western blot analysis. In addition, we found that downstream signals for caspase-9 and -3 activation were apparently blocked by antioxidant treatment at D3 and D5. Finally, we found that treatment with GSH and NAC reduced major capsid protein (MCP) expression and virus titer (TCID50%) by up to 15-fold at D5 in GF-1 cells. Thus, our data suggest that ISKNV can induce ROS production, which triggers Nrf2-mediated stress signals. Then, these stress signals can regulate mitochondrion-mediated Bax/Bak apoptotic signaling, which is connected to downstream caspase-9 and -3 activation. If ISKNV-induced Nrf2-mediated stress signaling is blocked, then the antioxidants GSH and NAC can also suppress apoptotic signals or reduce viral replication.